Sources of X-radiation based on stochastic acceleration of rare plasma particles - Antonov, A.N.; Buts, V.A.; Kovpik, O.F.; Kornilov, E.A.; Manuilenko, O.V.; Svichenskii, V.G.; Stepanov, K.N.; Tolstoluzhskii, A.P.; Turkin, Yu.A. (Вопросы атомной науки и техники, 2001)
The results of theoretical and experimental study of stochastic plasma heating are presented. The high efficiency of such heating is shown. The possibility of using such plasma as a source of X-radiation is analyzed. Such sources are compared with the closest known sources.